Research on Nature and Extent of Salt-affected Agricultural Soils in Ho – Keta Plain in the Volta Region of Ghana - L. Sackey; A. Sadick; F. M. Tetteh; E. O. Bennoah (Challenges and Advances in Chemical Science Vol. 7, 2021)
One of the major environmental issues that have severe adverse effect on sustainable agriculture productivity is soil salinization. A research was conducted at Ho-Keta plain in the Volta Region of Ghana to assess the extent of degradation of salt-affected agricultural soils. Two soil series, Oyebi and Ada in three salt-affected areas within the Lower Volta basin in the Ho-Keta plain were selected from Anyako, Anyenui and Atiehife. Soil sampling was done randomly at the depth of 0-30 cm from the soil sites and transported to the laboratory for analysis and measurement of pH (4.61) Calcium (5.60meq/l), Magnesium (3.17meq/l), Sodium (6.95meq/l), Potassium (1.83meq/l) and Electrical Conductivity (5.13dS/m) respectively. The mean values of Ca, Mg, Na and K were used to estimate Sodium Adsorption Ratio (SAR) and Exchangeable Sodium Percentage (ESP) respectively. The mean values of SAR and ESP in the three selected areas were: 43.89, 52.02, 42.85 and 33.87%, 40.77% and 37.83 5% respectively. The results revealed land degradation in the study area as a result of high levels of SAR and ESP leading to low soil chemical properties. The fertility level of the soil was very low and requires management practices that promote accumulation of organic matter. Further investigation to show the extent and the nature of soils in the study area is highly recommended.